Penerapan Pasal 112 Ayat (1) dan Pasal 127 Ayat (1) Huruf A Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika Dalam Kaitannya Dengan Surat Edaran Mahkamah Agung Nomor 3 Tahun 2015 - Dina Eriza Valentine Purba; Alvi Syahrin; Edi Yunara; M Eka Putra (Jurnal Ilmiah Penegakan Hukum, 2022)
This study aims to find out the essence of the importance of recording marriages in Muslim communities in Kampung Nangka Village, North Binjai. As mandated by Article 1 of Law no. 1 of 1974 concerning Marriage that marriage is an inner and outer bond of a man and a woman as husband and wife with the aim of forming a happy and eternal family based on God Almighty. One of the most important things to do is register the marriage. The fact is that in the community, especially in remote areas, marriage registration in official state documents is rarely done. This research is a normative legal research with analytical descriptive nature by using a literature approach and a field approach. Analysis of the data obtained in this study was carried out qualitatively. The results of the study indicate that the problem of the lack of marriage registration is caused by several factors, such as the lack of knowledge of some people to the laws and regulations regarding marriage, both from the Islamic legal aspect and the positive legal aspect, the existence of some people who still carry out unregistered marriages for various reasons. This can prevent problems that can harm one party if the marriage is not recorded. Many people do not understand the importance of registering marriages that have been carried out and the consequences because marriages are not registered